Metronidazole enhances killing of Porphyromonas gingivalis by human PMNs - Serbanescu, Mihaela Anca; Oveisi, Morvarid; Sun, Chunxiang; Fine, Noah; Bosy, Anne; Glogauer, Michael (Frontiers in Oral Health, 2022)
Background and objectives Periodontitis affects the supporting structures of the teeth as a result of the interactions between the subgingival biofilm and the host immune system. Periodontal therapy in severe forms of periodontitis often utilizes antimicrobial agents with some potential to improve host defense responses. In the present study, we investigated the in vitro effect of metronidazole (MTZ) at concentrations achievable in the periodontal pocket on PMN activation and PMN mediated killing of Porphyromonas gingivalis. Materials and methods Flow cytometry based assays were used to measure the impact of MTZ on PMN degranulation, neutrophil extracellular trap (NET) formation and myeloperoxidase (MPO) release and phagocytosis in response to the keystone oral pathogen P. gingivalis. Functional assays for PMN mediated killing of P. gingivalis and reactive oxygen species (ROS) production in PMN were also carried out. Results We demonstrate that PMNs pretreated with MTZ (2 μg/ml or 50 μg/ml) displayed enhanced killing of P. gingivalis compared to untreated PMNs. At concentrations achieved physiologically in the periodontal pocket, MTZ induced PMN surface expression of two activation markers (CD66 and CD63). MTZ did not alter P. gingivalis-induced NETosis, but suppressed P. gingivalis-induced ROS production and phagocytosis. Conclusion MTZ displays a positive interaction with PMNs to potentiate PMN mediated killing of P. gingivalis and may therefore contribute to its beneficial effects in the treatment of periodontitis initiated by P. gingivalis infections including those refractory to conventional treatment.